MODELING OF A THIN-LIQUID FALLING-FILM IN ABSORPTION COOLING SYSTEMS (2012)
Absorption refrigeration systems are generally characterized by low Coefficient of Performance (COP). Absorption enhancement is an effective way of improving the COP of refrigeration systems. Literature is sparse on the use of magnetic field for the enhancement of absorption refrigeration systems despite its cheapness and environmental friendliness as compared with other enhancement methods. Although the method has recently been employed on ammonia solution, its influence on lithium bromide (LiBr) and lithium chloride (LiCl) solutions is yet to be fully studied. In this study a numerical model for the magnetic field enhancement of the absorption cooling-system using LiBr and LiCl solutions was developed and evaluated. The flow within the film thickness to the absorber wall was considered as a two-dimensional steady laminar flow. A Finite Difference model was developed based on conservation of mass, momentum, energy equations and mass transport relationship. The model was validated using data from the literature on ammonia solution. Standard parameters including absorber wall length (1 m), film thickness (10-3 m), magnetic field vacuum permeability (1.257 x 10-6 kgmA-2s2), magnetic mass susceptibilities and magnetic induction intensities were used for LiBr and LiCl solutions' modeling. Changes in their concentrations, both in the direction of falling film and across its thickness, were investigated. Data were analysed using descriptive statistics and Student's t-test (p=0.05). The concentration distribution for ammonia solution within the film thickness was not significantly different from results in the literature. For the magnetic induction range of 0.0 and 3.0 Tesla, the concentration distribution of LiBr solution in the direction of falling film was between 54.9% and 60.0%, while that of LiCl solution ranged between 39.9% - 45.0%. Meanwhile, across the film thickness and for the same range of magnetic induction of 0.0 and 3.0 Tesla, the concentration distribution for LiBr solution was between 0.0 and 0.19 and those of LiCl solution were between 0.0 and 0.13. The concentration of LiBr solution increased from 0.0 to 4.7 and 0.0 to 21.7 when magnetic induction was increased from 0.0 to 1.4 and 0.0 to 3.0 Tesla, respectively. Similarly for LiCl solution, increased values of 0.0 to 3.3 and 0.0 to 15.5 were obtained when magnetic induction was increased from 0.0 to 1.4 and 0.0 to 3.0 Tesla, respectively. In both cases, it implies higher cooling effect. Relative to 0.0 Tesla, the COP of LiBr and LiCl solutions absorption refrigeration systems was increased by 0.1% when magnetic induction was 1.4 Tesla, while increment of 0.3% and 0.2% respectively were obtained when magnetic induction was 3.0 Tesla. The percentage increments in COP of LiBr solution were not significantly different from that of the LiCl solution. Magnetic field enhanced the absorption performance in the lithium bromide and lithium chloride solutions; hence can be used in typical absorption refrigeration systems.